Gradnik in slikarji - Hladnik, Miran (Slavistična revija, 2006)
Alojz Gradnik followed with great care the artistic design of his books. He most intensively worked and associated with the painters Fran Tratnik, Božidar Jakac, Miha Maleš, Riko Debenjak, and Elko Justin, while he considered Rihard Jakopič the herald of his artistic views. Gradnik's poetic-graphic portfolios have the status of bibliophile editions, and his collection De profundis was in 1926 considered a volume with the finest artistic design in the entire Slovene literary production.
Keywords: bibliofilske izdaje; Gradnik, Alojz, 1882-1967; grafične izdaje; ilustracije; pesniški listi; Slovene literature; slovenska književnost; slovenska poezija